Workload Dimensions of Kitchen Workers and Their Health Impacts: A Systematic Review Based on NASA-TLX - Witasari, Neli; Wardani, Yuniar; Hariyono, Widodo Hariyono (Reflection Journal, 2026)
Kitchen workers face significant workloads due to exposure to high temperatures, long working hours, and non-ergonomic postures, putting them at risk of fatigue, musculoskeletal disorders, heat stress, and chronic exhaustion. This study aims to summarize the latest findings on the impact of workloads on kitchen workers based on the six dimensions of NASA-TLX. The study design is a quantitative systematic review of the last five years through PubMed and Google Scholar, following the PRISMA guidelines for the selection process. A total of 11 articles met the inclusion criteria. The results show that physical workload, including prolonged standing, repetitive movements, and non-ergonomic postures, is significantly associated with musculoskeletal disorders, with a prevalence of 92.3%. Working hours exceeding 8 hours are linked to fatigue, increased presenteeism, and a decreased quality of life, while heat stress was reported as a major health concern. Support from coworkers was found to mitigate the impact of physical and psychosocial workload. In conclusion, improvements in ergonomics, work hours and shift arrangements, increased ventilation, and enhanced psychosocial support are necessary to mitigate health risks associated with excessive workloads among kitchen workers.